2011
DOI: 10.3857/jkstro.2011.29.1.36
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Therapy for Hepatocellular Carcinoma with Portal Vein Tumor Thrombosis

Abstract: Purpose: To evaluate the effectiveness of radiation therapy (RT) for hepatocellular carcinoma (HCC) with portal vein tumor thrombosis (PVTT) and to analyze the prognostic factors. Materials and Methods: From December 2004 to April 2009, 70 patients who had HCC with PVTT were treated with RT at Keimyung University Dongsan Medical Center. Nineteen patients whose total dose was below 30 Gy and one patient who underwent liver transplantation were excluded. The remaining 50 patients (45 males, 5 females; median age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 32 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…Although randomized trials are lacking, several studies have reported the efficacy of combined treatment with TACE and RT in patients with advanced HCC [ 7 , 8 , 9 , 14 , 15 , 16 , 17 , 18 ]. A response rate of 25% to 76% and a median survival of 5.3 to 20 months have been reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although randomized trials are lacking, several studies have reported the efficacy of combined treatment with TACE and RT in patients with advanced HCC [ 7 , 8 , 9 , 14 , 15 , 16 , 17 , 18 ]. A response rate of 25% to 76% and a median survival of 5.3 to 20 months have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Although several institutions have reported favorable outcomes with this combined treatment approach [ 7 , 8 , 9 , 14 , 15 , 16 , 17 , 18 ], interpreting the results of these studies is controversial due to heterogeneity in study populations, histories of prior treatments, and the strategies used to combine TACE and RT. The purpose of this study was to evaluate the efficacy of combined TACE followed 2 weeks later by RT among treatment-naïve patients with BCLC stage C of which prognosis was validated in several studies [ 19 , 20 ] to limit potential confounding effects by prior treatments for HCC and heterogeneity of study population.…”
Section: Introductionmentioning
confidence: 99%